Quantification of lipid modified estrogenic derivative (ESC8) in rat plasma by LC‐MS: application to a pharmacokinetic study. (24th July 2016) - Ahmad, Ajaz; Mondal, Sujan Kumar; Jan, Basit Latief; Mukhopadhyay, Debabrata; Banerjee, Rajkumar; Alkharfy, Khalid M.
Abstract: A lipid‐conjugated, estrogenic derivative molecule, ESC8, compared with other estrogenic molecules, encourages cell death in both ER‐positive and ER‐negative breast cancer cells. A rapid and highly sensitive assay method has been developed and validated for the estimation of a ESC8 in rat plasma using liquid chromatography coupled with mass spectrometry under positive‐ion mode with electrospray ionization. The sample process includes using methanol for precipitation of ESC8 and dextromethorphan (internal standard, IS) from plasma. Chromatographic separation was achieved with methanol–water–formic acid (70:30:0.1% v/v/v) pumped at a flow rate of 0.3mL/min and a C18 column (50 × 2.1 mm i.d., 1.7 μm particle size) with a total run time of 5 min. The m / z ions monitored were 568.5 and 272.1 for ESC8 and IS, respectively. The lower limit of quantitation achieved was 1.08 ng/mL and linearity was observed from 5 to 500 ng/mL. The intra‐ and inter‐day precisions were <4%. The proposed method was successfully applied to a preliminary pharmacokinetic study of ESC8 liposomal formulation following an intraperitoneal administration of 3.67 mg/kg in rats. The concentrations of ESC8 in plasma were quantifiable up to 36 h. The peak concentration of ESC8 was found to be 110.72 ng/mL, the area under the concentration–time curve was 1625.23ng/mL h and the half‐life was 11.72 h.